2023
DOI: 10.1002/apj.2950
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fe–N–C morphologies on the oxygen reduction reaction in acidic and alkaline media

Abstract: The development of nonnoble metal oxygen reduction reaction (ORR) catalysts for fuel cells has been motivated by the high cost and limited supply of noble metals, as well as the desire to improve the performance and durability of this type of energy conversion device. In this study, nonnoble Fe–N–C catalyst was synthesized using a zeolitic imidazole framework (ZIF‐8), poly (aniline), and 10,10′‐dibromo‐9,9′‐bianthry as precursors to produce Fe–N–C with hollow sphere (HS), amorphous bulky structure (B), and she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 91 publications
(183 reference statements)
0
1
0
Order By: Relevance
“…They found that the calcium stearate Pickering W/O emulsion system is suitable for a long‐term “open” cultivation of microorganisms without the use of any special equipment such as a jar‐fermenter. Junaidi et al 16 used highly porous Fe–N–C hollow sphere catalyst with demonstration active site activation and excellent stability compared with the other samples as well as commercial Pt/C in acidic electrolyte, which suggests its potential for application in proton exchange membrane fuel cells (PEMFCs).…”
mentioning
confidence: 99%
“…They found that the calcium stearate Pickering W/O emulsion system is suitable for a long‐term “open” cultivation of microorganisms without the use of any special equipment such as a jar‐fermenter. Junaidi et al 16 used highly porous Fe–N–C hollow sphere catalyst with demonstration active site activation and excellent stability compared with the other samples as well as commercial Pt/C in acidic electrolyte, which suggests its potential for application in proton exchange membrane fuel cells (PEMFCs).…”
mentioning
confidence: 99%